2016
DOI: 10.24972/ijts.2016.35.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Seen: A Pathway to Transformation

Abstract: Chronic exposure to racial indignities can engender a subjective sense of invisibility, in which an individual feels that the dominant culture fails to recognize one's worth, abilities, and talents. The sense of feeling unseen can permeate myriad aspects of the lived experience and negatively impact well-being. Using the case of an African American male in therapy with an African American female psychotherapist, this article presents how implicit and explicit acts of recognition of the patient and acknowledgme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Towards that end, I want to bring in the core constructs identified by Owen (2013) and his colleagues (Davis et al, 2018;Owen et al, 2017Owen et al, , 2018 as central in the multicultural orientation framework. I also want to bring into the discussion two other published systematic case studies of successful AEDP therapies with clients identified as belonging to oppressed minorities (Medley, 2018;Simpson, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Towards that end, I want to bring in the core constructs identified by Owen (2013) and his colleagues (Davis et al, 2018;Owen et al, 2017Owen et al, , 2018 as central in the multicultural orientation framework. I also want to bring into the discussion two other published systematic case studies of successful AEDP therapies with clients identified as belonging to oppressed minorities (Medley, 2018;Simpson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To further evaluate AEDP from within a multicultural orientation framework, in addition to Vigoda Gonzalez's case of Rosa, we have two other published, systematic case studies documenting effective AEDP therapies with clients who are members of oppressed minorities: Simpson's (2016) successful AEDP treatment of an African American man and Medley's (2018) successful AEDP therapy with a male client self-identified as gay. In both therapies, the application of AEDP techniques informed by its fundamentally healing orientation and affirmative ethos allowed corrective emotional experiences for both clients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An affirmative, deliberately positive, attuned and relationally reparative therapeutic stance (Lipton & Fosha, 2011) is required to bring this disposition to the clinical fore. AEDP's healing-oriented, change-based metapsychology reflects a seamless, organic, holistic integration (Fosha & Yeung, 2006) of many sources: neuroplasticity research; affective neuroscience; attachment theory and research on developmental dyads; interpersonal neurobiology; emotion theory; memory reconsolidation; transformational studies; contemplative practices; other experiential, existential and somatic trauma treatments; and two decades of systematic qualitative research on the therapy videotapes of a growing number of certified AEDP practitioners worldwide (Fosha, 2017a;Fosha, Paivio, Gleiser & Ford, 2009;Gleiser, Ford & Fosha, 2008;Hanakawa, 2017Hanakawa, , 2018Klein, 2018;Lamagna, 2011;Lamagna & Gleiser, 2007;Lipton & Fosha, 2011;Medley, 2018;Ofer & Gross, 2017;Prenn, 2011;Prenn & Slatus, 2018;Russell, 2015;Simpson, 2016;Sundgren, 2014;Yamauchi, 2018;Yeung & Cheung, 2008).…”
Section: Introductionmentioning
confidence: 99%